Validity of hand-to-foot measurement of bioimpedance: Standing compared with lying position - Rush, E. C.; Crowley, J.; Freitas, I. F.; Luke, A. (North Amer Associação Study Obesity, 2006)
Objective: To assess the reliability of the standing measurement of hand-to-foot bioimpedance compared with measurements made in the lying position.Research Methods and Procedures: In 205 volunteers 6 to 89 years of age, 111 males and 94 females from six ethnic groups, effects of posture, time, and age on hand-to-foot resistance were studied over a range of body size. The effect of time in a position on resistance was also recorded in a small subset (n = 10), and repeat measurements over 3 days at the same time of the day were recorded in another subset (n = 12).Results: Lying impedance was consistently higher than standing, with the relationship (resistance lying/resistance standing) for the children (5 to 14 years) being 1.031, progressing to a ratio of 1.016 in those >60 years. The time spent static in either position did change resistance measurements - a decrease of up to 9 Omega (mean 5 Omega, 1.0%) over 10 minutes of standing and an increase of up to 7 Omega (mean 3 Omega, 0.7%) with lying.Discussion: In the field, measurements of hand-to-foot bioimpedance can be made in the standing position, and, with appropriate adjustment, previously validated recumbent equations can be used. Given that errors in the measurement of height and weight also affect the reliability of the derivation of body fat from bioelectrical conductance, the errors that may arise from a more practical standing measurement rather than lying are minimal.
Keywords: single frequency bioimpedance analysis; position; lying; standing; correction factor